Pius Stephen Ekong1, Raymond Juryit2, Ndahi Mwapu Dika3, Patrick Nguku4, Monica Musenero5 - Pius Stephen Ekong; Raymond Juryit; Ndahi Mwapu Dika; Patrick Nguku; Monica Musenero (The Pan African Medical Journal, 2012)

(untitled)
BACKGROUND: Zoonotic infections are among the most common on earth and are responsible for over 60% of human infectious diseases, some of which are caused by helminth parasites. Infection may result from ingestion of infective stage of worms with food, contaminated soil; skin penetration or direct animal contact. This study estimates the prevalence of zoonotic helminth infections (ZHI) among animals and humans in Jos and identifies associated risk factors. METHODS: We reviewed laboratory records from five hospitals, one veterinary clinic and meat inspection record at abattoir in Jos from 2005 - 2009. Prevalence was defined as the observed frequency of cases of zoonotic helminth in the sampled population within the study period. Odd ratio analysis was used to identify factors associated with ZHI. RESULTS: Of 6689 humans tested, 524 (7.8%) were positive. Observed ZHI are: Ascaris species (4.5%), Taeniasis-Cysticercosis (1.5%), Schistosoma species (1.1%), Strongyloidosis (0.09%). Among animals, 3520 (18.1%) of 19508 tested/observed were positive; including Fasciola species (12.7%), Taeniasis-Cysticercosis (5.0%), Strongyloidosis (0.4%), Ascaris species (0.04%). The risk of infection was higher among humans aged 6-19 (OR: 3.2; 95% CI: 2.0-5.2) and 20-60 (OR: 2.3; 95% CI: 1.7-3.9). Peri-urban dwellers are at higher risk (OR: 1.5; 95% CI: 1.3-1.9); and so are farmers. CONCLUSION: The prevalence of zoonotic helminth infection is high among humans and animals in Jos. Risk of infection are higher among human age 6-60, peri-urban dwellers and farmers. This calls for the formulation of workable collaboration between human and veterinary medical disciplines for better control of zoonotic helminth infections.